Implementation of Occupational Health And Safety Management System At Perumda Tirtanadi North Sumatra Province - Sinambela, Ika Mariani; Ahmad Hafizullah Ritonga; Basyariah Lubis (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Occupational Safety and Health (K3) is an effort made so that workers always work safely and healthily in the workplace, and resources and production processes can be used safely and efficiently. The number of work accident cases in Indonesia in the period January-August 2024 was 278,564 cases, of which North Sumatra Province had 15,220 cases. Every company is required to implement an Occupational Safety and Health Management System (SMK3) that is integrated with the company's management system. The implementation of the occupational safety and health management system (SMK3) at Perumda Tirtanadi, North Sumatra Province has a good management system, this is proven by the certification audit process by the K3 management system audit institution by PT. Surveyor Indonesia and has received recognition from the Indonesian Ministry of Manpower. This study aims to determine five (5) principles, namely the determination of K3 policies, K3 planning, implementation of K3 plans, monitoring and evaluation of K3 performance, and review and improvement of K3 performance at Perumda Tirtandi. This study uses a descriptive qualitative approach through interviews. The interview results were processed using the NVIVO application. The results of the study are on the first principle of establishing K3 policies by establishing SOPs and annual work programs in accordance with national regulations, which must be informed to all employees. The second principle is K3 planning which emphasizes K3 culture through repeated socialization reflecting an ecological-social approach in health promotion. The third principle, namely the implementation of K3 in Perumda Tirtanadi shows a strong commitment to ensuring the use of PPE and compliance with K3 signs. The fourth principle, sustainability in SMK3 is reflected in the monitoring system of Perumda Tirtanadi, which involves visits from management and the K3 advisory committee. The fifth principle is a critical process that allows management to conduct objective assessments of the entire system. The study on the Implementation of the Occupational Safety and Health Management System (SMK3) requires socialization of SMK3 and considers K3 as something mandatory and a necessity when working.